2009
DOI: 10.1186/1471-2164-10-196
|View full text |Cite
|
Sign up to set email alerts
|

Molecular profiles of Quadriceps muscle in myostatin-null mice reveal PI3K and apoptotic pathways as myostatin targets

Abstract: Background: Myostatin (MSTN), a member of the TGF-β superfamily, has been identified as a negative regulator of skeletal muscle mass. Inactivating mutations in the MSTN gene are responsible for the development of a hypermuscular phenotype. In this study, we performed transcriptomic and proteomic analyses to detect altered expression/abundance of genes and proteins. These differentially expressed genes and proteins may represent new molecular targets of MSTN and could be involved in the regulation of skeletal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
53
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 67 publications
7
53
1
1
Order By: Relevance
“…Signatures related to muscle energy metabolism and growth As expected (Bouley et al, 2005;Cassar-Malek et al, 2007;Chelh et al, 2009b), our results revealed additional evidences of glycolytic shift within skeletal muscle in the absence of functional MSTN with increased abundance of fast-twitch proteins (e.g. H-MyBP and PGM1) and decreased abundance of H-FABP in DM muscles.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…Signatures related to muscle energy metabolism and growth As expected (Bouley et al, 2005;Cassar-Malek et al, 2007;Chelh et al, 2009b), our results revealed additional evidences of glycolytic shift within skeletal muscle in the absence of functional MSTN with increased abundance of fast-twitch proteins (e.g. H-MyBP and PGM1) and decreased abundance of H-FABP in DM muscles.…”
Section: Discussionsupporting
confidence: 78%
“…In an earlier study, comparing molecular profiles in the muscles of MSTN-null mice v. their controls, we found differential expression of many genes and proteins related to muscle energy metabolism, activation of the PI3K/Akt signalling pathway and cell survival/apoptosis pathway (Chelh et al, 2009b). In this study, we examined some components of these pathways in the muscles of DM foetuses and DM cows harbouring MSTN loss-of-function.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations